An analysis of information visualisation - Chen, Min; Floridi, Luciano (Synthese (Dordrecht), 2013)
Philosophers have relied on visual metaphors to analyse ideas and explain their theories at least since Plato. Descartes is famous for his system of axes, and Wittgenstein for his first design of truth table diagrams. Today, visualisation is a form of 'computer-aided seeing' information in data. Hence, information is the fundamental 'currency' exchanged through a visualisation pipeline. In this article, we examine the types of information that may occur at different stages of a general visualization pipeline. We do so from a quantitative and a qualitative perspective. The quantitative analysis is developed on the basis of Shannon's information theory. The qualitative analysis is developed on the basis of Floridi's taxonomy in the philosophy of information. We then discuss in detail how the condition of the 'data processing inequality' can be broken in a visualisation pipeline. This theoretic finding underlines the usefulness and importance of visualisation in dealing with the increasing problem of data deluge. We show that the subject of visualisation should be studied using both qualitative and quantitative approaches, preferably in an interdisciplinary synergy between information theory and the philosophy of information.